POLA KOMUNIKASI KELUARGA DAN PERKEMBANGAN EMOSI ANAK (STUDI KASUS PENERAPAN POLA KOMUNIKASI KELUARGA DAN PENGARUHNYA TERHADAP PERKEMBANGAN EMOSI ANAK) - Arie Pratama (Jurnal Ilmiah Hospitality, 2022)
This research aimed to describing the communication pattern taking place inside Javanese families in Sleman regency and city of Jogjakarta. It also to discover the extent to which Javanese families understood and realized the importance of family communication and child emotional development, and the impact of family communication on child emotional development. This research was using descriptive–qualitative method and based on symbolic interactionism theory. Data were collected by using a passive observation technique and by conducting in-depth interviews with 18 informans. Informans were taken by employing a purposive sampling and selected based on their accessibility to the studied issue. Data were analyzed using interactive analysis model.